Jump and Crawl Game Development to Stimulate the Balance of 5-6 Year Olds - Berliana Ramadhanti; Pramono Pramono; Munaisra Tri Tirtaningsih (BIRCU, 2022)
Early Childhood Education is defined as one of the various fields of education starting at the age of 0 (from birth) to the age of 6 years which provides learning activities by taking into account the characteristics of the child. This research aims to produce an effective, efficient and interesting Jump and Crawl game product. This game is focused on stimulating the balance of children aged 5-6 years which is equipped with a guide book. This type of research is Research and Development (RnD) using the ADDIE model. Assessment criteria from the aspect of efficiency, effectiveness and attractiveness. The instrument of quantitative data analysis technique was obtained from the validity of the material and the validity of the game development. The results of accumulated validity from several experts yield a percentage of 90.3% which means it is very feasible to use. The trial used small and large groups with the criteria for assessing effectiveness, efficiency and attractiveness. Qualitative data were obtained from interviews with two kindergarten schools in Blitar Regency. Researchers found that the Jump and Crawl game had three eligibility criteria, namely interesting, effective, and efficient to stimulate the balance of children aged 5-6 years.